2017
DOI: 10.13189/ujm.2017.051002
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Government Policies on the Relationship between Technology, Innovation and Entrepreneurship Development in Nigeria: A Partial Least Square Approach

Abstract: Given the economic realities in Nigeria, the country must constantly create new jobs, and diversify the industrial and commercial sector to take advantage of human and natural resources through entrepreneurship development. The present research aims to identify the role of government policies on the relationship between innovations, technology and entrepreneurship development in Nigeria. Questionnaire was distributed to Small and Medium Scale Enterprises (SMEs) in Osun State. Structural Equation Model was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…public investments, TDZs and ICTs) played a positive and significant role in differentiating regions that are able to sustain high entrepreneurship rates from other categories. These results supported the hypothesis of the paper and are consistent with the previous findings of the existing empirical literature; positive and significant associations between entrepreneurship level and human capital, financial capital, agglomeration, migration and government policies and measures (Glaeser et al, 2014;Audretsch et al, 2015;Simoes et al, 2016;Dvouletý and Mareš, 2016;Oyelakin and Kandi, 2017;Prieger et al, 2017;Urban and Ratsimanetrimanana, 2019). Contrarily, the regions having a weak performance in entrepreneurship levels (Category 1) are characterized by low levels of innovativeness, loss of population and low levels of exports, although they received higher levels of government incentives in the 2000-2011 period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…public investments, TDZs and ICTs) played a positive and significant role in differentiating regions that are able to sustain high entrepreneurship rates from other categories. These results supported the hypothesis of the paper and are consistent with the previous findings of the existing empirical literature; positive and significant associations between entrepreneurship level and human capital, financial capital, agglomeration, migration and government policies and measures (Glaeser et al, 2014;Audretsch et al, 2015;Simoes et al, 2016;Dvouletý and Mareš, 2016;Oyelakin and Kandi, 2017;Prieger et al, 2017;Urban and Ratsimanetrimanana, 2019). Contrarily, the regions having a weak performance in entrepreneurship levels (Category 1) are characterized by low levels of innovativeness, loss of population and low levels of exports, although they received higher levels of government incentives in the 2000-2011 period.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies evaluated the level of effectiveness of existing policies, including the ones indicating the positive contribution to regional entrepreneurship, besides the ones sceptical about their level of effectiveness. According to Mason and Brown (2011), Ostapenko (2016) and Oyelakin and Kandi (2017) government policies contribute positively to the promotion and development of regional entrepreneurship. Contrarily, Ihugba et al (2014), Onwuka et al (2014) and Tende (2014) underline the insignificant influence of policy measures on the formation of entrepreneurial activities, especially due to problems concerning credit policies and measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, Oyelakin and Kandi (2017) showed that government policies has moderating role on the relationship between innovation, technology and entrepreneurship development. Government policies affect entrepreneurship development directly and indirectly (29), (31).…”
Section: The Interaction Of Government Support and Owner Characteristics To E-commerce Adoptionmentioning
confidence: 99%
“…The comparison of AVE square root results with inter-construct correlations can be seen through The Fornell-Larcker Criterium. The Fornell-Larcker Criterium is a common and conservative approach to asses dicriminant validity and it can be applied in PLS-SEM (29). The diagonal value is the square root of AVE, while other values are the correlations between the respective latent construct.…”
Section: Evaluation Of Measurement Model (Outer Model)mentioning
confidence: 99%